The Influence of Product and Facade Design towards Its Selling Price - Imanuel Mbake; Christiono Utomo; Purwanita Setijanti (IPTEK Journal of Proceedings Series, 2015)
Pricing become one of determinant variable of consumer preferences to product and design of a house. When the selling price of a house is highest than the buying power of consumer, then the number of its demand was go down. Conversely, when the selling price of house could reachable by consumer buying power, then the number of its demand increased. This research is the preliminary research from advanced research to investigate the marginal pricing of Perumahan Pondok Indah Matani. By literature reviews and cost calculation methods, it is found that there were three (3) aspect of product and facade design of house that influences to the selling price, namely cost of spouse and plastering walls, cost of door sills and windows; and wall-painting cost.